The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1093/jpids/piw009
|View full text |Cite
|
Sign up to set email alerts
|

Use of Tigecycline in Pediatric Patients With Infections Predominantly Due to Extensively Drug-Resistant Gram-Negative Bacteria

Abstract: Tigecycline, given at the range of administered doses as salvage therapy and in combination with other antimicrobial agents, seemed to be well tolerated in a series of mainly critically ill pediatric patients and demonstrated relatively good clinical response in nonbacteremic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 27 publications
1
48
1
7
Order By: Relevance
“…However, off‐label use of TGC is widely adopted in critically ill adults, especially for infections caused by MDR/XDR pathogen . In real‐world clinical practice, successful cases are also reported for off‐label use of TGC in children, especially for infections caused by MDR/XDR bacteria . Pediatricians usually prescribe TGC as salvage therapy in serious infections.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, off‐label use of TGC is widely adopted in critically ill adults, especially for infections caused by MDR/XDR pathogen . In real‐world clinical practice, successful cases are also reported for off‐label use of TGC in children, especially for infections caused by MDR/XDR bacteria . Pediatricians usually prescribe TGC as salvage therapy in serious infections.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 In real-world clinical practice, successful cases are also reported for off-label use of TGC in children, especially TA B L E 2 Susceptibility testing results of K pneumoniae (n = 9) and A baumannii (n = 4) isolates to antimicrobial agents for infections caused by MDR/XDR bacteria. [11][12][13] Pediatricians usually prescribe TGC as salvage therapy in serious infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all of the available data regarding the use of tigecycline in infants and children younger than 8 years derive from small case series collected retrospectively. [3][4][5][6][7]10 Although optimal dosage has not been defined, the usual dose reported in different case series ranged from 1 to 2 mg/kg every 12 hours. 1 In a case report of 12-month old liver transplant recipient with XDR Acinetobacter baumannii bacteremia, it was found that a dose of 1 mg/kg every 12 hours (without loading dose) provided similar drug exposure (area under the curve, AUC) with adult and children aged 8 to 11 years old.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The off-label use of tigecycline to treat serious infections (blood stream infections, urinary tract infections, nosocomial pneumonia, or meningitis) has been reported in the pediatric age group. [3][4][5][6][7] The majority of patients in these clinical series were beyond infancy, and it was stated that tigecycline was generally well tolerated except for gastrointestinal adverse events (nausea, vomiting, diarrhea, acute pancreatitis), prolonged coagulation times, and mild increase of transaminases. [3][4][5][6]8 However, there is only scant information on tigecycline use in newborn infants.…”
Section: Introductionmentioning
confidence: 99%